Hijri calendar effect in Borsa Istanbul gold market and Turkey's foreign exchange market. Issue 4 (8th July 2019) - Ozkan, Nasif
Abstract : Purpose: This study aims to investigate the Hijri calendar effect in Borsa Istanbul (BIST) precious metal market and foreign exchange market (Dollar and Euro market) of Turkey. Design/methodology/approach: The data of BIST gold market index and foreign exchange market are used for the period of 4 March 2003-30 September 2016 (1 Muharram 1424 – 28 Dhu al-Hijja 1437) in the study. These data are analyzed by using the dummy variable regression model and Kruskal–Wallis (KW) test. Findings: The results of the regression models and KW test indicate that there is a Ramadan effect in the gold market and after-Ramadan effect in the Euro market. On the other hand, the Hijri month effect does not exist in the Dollar market. Originality/value: This is the first paper that investigates the Hijri calendar effect in gold and foreign exchange markets of Turkey other than the stock market.